Telomere length and TERT polymorphisms as biomarkers in asbestos-related diseases - Mervič, Ana (Radiology and oncology (Ljubljana), 2024)
Asbestos exposure has been proposed as a risk factor for shorter telomere length. The aim of our study was to investigate whether telomere length in leukocytes and hTERT genetic polymorphisms may serve as potential biomarkers for the risk of developing asbestos-related diseases and as biomarkers of progression and chemotherapy response rate in malignant mesothelioma (MM). Subjects and methods. We conducted two retrospective studies. In the first study, a case-control study, telomere length and hTERT polymorphisms were determined in patients with MM, subjects with pleural plaques and controls without the asbestos related disease, who were occupationally exposed to asbestos. In the second study, a longitudinal observational study, telomere length was also determined in samples from MM patients before and after chemotherapy. Telomere length was determined by monochromatic multiplex quantitative polymerase chain reaction (PCR), while competitive allele-specific PCR was used to genotype hTERT rs10069690, rs2736100 and rs2736098. Logistic regression and survival analysis were used in statistical analysis. Results. Patients with MM had shorter telomere length than subjects with pleural plaques (p 0.05) or time to disease progression (p > 0.05). Carriers of one or two polymorphic rs10069690 T alleles had a good response to chemotherapy (p = 0.039, and p = 0.048), these associations remained statistically significant after adjustment for age (padj = 0.019; padj = 0.017). Carriers of two polymorphic rs2736100 A alleles had a longer time to disease progression (p = 0.038). Conclusions. Shorter telomere length and hTERT polymorphisms may serve as a biomarker for the risk of developing MM. Additionally, rs10069690 and rs2736100 polymorphisms, but not telomere length, were associated with a chemotherapy response or MM progression.
Keywords: asbestos; azbestoza; dolžina telomer; malignant mesothelioma; maligni mezoteliom; telomere length